Development and validation of the Economic Coercion Scale-20 (ECS-20): A short-form of the ECS-36. - Stephanie Spaid Miedema; Yuk Fai Cheong; Ruchira Tabassum Naved; Kathryn M Yount (PLoS ONE, 2023)
The Economic Coercion Scale 36 (ECS-36) is a validated scale measuring women's exposure to economic coercion for low-income countries. A valid short form is needed to facilitate parsimonious measurement of economic coercion in general surveys or program evaluations. We used data from a probability sample of 930 married women 15-49 years in Matlab, Bangladesh. We selected 21 items from the ECS-36 based on theory, content coverage, and item and dimensional information. We evaluated external validity with measures of non-economic intimate partner violence and depressive symptoms. We tested measurement invariance of the short-form scale across participants and non-participants of microfinance programs. A final, 20-item scale captured husband's interference with wife's (1) acquisition of economic resources and (2) use or maintenance of economic resources. IRT results of the ECS-20 demonstrated precision over the higher range of the economic coercion trait. Tests of external validity confirmed expected correlations of the ECS-20 with measures of IPV and depressive symptoms. The ECS-20 was measurement invariant across groups of women who did and did not participate in microfinance programs. The ECS-20, a valid short-form of the ECS-36, is suitable for general surveys and monitoring potential adverse impacts of microfinance programs targeting women.